Assessing Students’ Online Learning Readiness: Are College Freshmen Ready? - Fearnley, Marissa R. (Animo Repository, 2021)
Advancements in technology and pedagogy with respect to distance education have highlighted the need for higher education institutions to adapt to these changes and embrace online learning as an alternative approach to instructional delivery. To assess students’ readiness to this non-conventional modality, the current study utilized the online learning readiness scale (OLRS) by administering an online version of the instrument to 457 college freshmen in a private college. The overall mean scores and standard deviations obtained for the five dimensions of online learning readiness are as follows: motivation for learning (x̄ = 4.23, SD = 0.61), computer/Internet self-efficacy (x̄ = 4.05, SD = 0.64), online communication self-efficacy (x̄ = 3.76, SD = 0.75), self-directed learning (x̄ = 3.74, SD = 0.63), and learner control (x̄ = 3.41, SD = 0.68). Nonparametric tests were employed to examine differences in the OLRS dimensions based on sex, academic program, and duration of Internet use. No significant difference in online learning readiness between male and female students was detected using Mann-Whitney U test. A similar test performed on the duration of Internet use found that students who spend more than four hours online have significantly higher computer/Internet self-efficacy scores. Moreover, the results of Kruskal-Wallis H test revealed that students’ academic programs pose significant differences in three dimensions, namely, computer/Internet self-efficacy, online communication self-efficacy, and motivation for learning. Overall, the results reflect positively on the readiness of freshman students for online learning.